2020
DOI: 10.1038/s41598-020-71047-1
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of mirror-induced self-directed behaviour on wildlife at the Royal Belum Rainforest Malaysia

Abstract: Mirror-induced behaviour has been described as a cognitive ability of an animal to self-direct their image in front of the mirror. Most animals when exposed to a mirror responded with a social interactive behaviour such as aggressiveness, exploratory and repetitive behaviour. The objective of this study is to determine the mirror-induced self-directed behaviour on wildlife at the Royal Belum Rainforest, Malaysia. Wildlife species at the Royal Belum Rainforest were identified using a camera traps from pre-deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…What determines an animal’s aggressive interaction with its own mirror image? Exposing different species to a mirror has revealed that mirror aggression is a common behaviour [ 36 38 ]. However, the amount of time spent mirror fighting varies between individuals of the same species suggesting that both intrinsic and extrinsic factors influence its expression.…”
Section: Discussionmentioning
confidence: 99%
“…What determines an animal’s aggressive interaction with its own mirror image? Exposing different species to a mirror has revealed that mirror aggression is a common behaviour [ 36 38 ]. However, the amount of time spent mirror fighting varies between individuals of the same species suggesting that both intrinsic and extrinsic factors influence its expression.…”
Section: Discussionmentioning
confidence: 99%
“…Horses have been tested via 'scraping' behavior of a mark on the cheek [58]. Elephants are considered to pass if they make a trunk-directed response [59][60][61].…”
Section: Sfr In Animalsmentioning
confidence: 99%
“…Natural salt licks are mineral rich deposits that play a significant role in the ecosystem of the tropical rainforest. Similarly, the importance of salt lick in terms of physiological well-being of animals of plant-based diets is well documented 1 6 and utilization should not be affected by sex and age categories. In addition, topography has been suggested to affect the accessibility of certain prey to utilize the salt lick due to the changes in mineral content of the salt lick area 2 , 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The Royal Belum Rainforest in Malaysia has been established as one of habitat for Malayan tiger and houses majority of others fauna species including the barking deer or muntjac ( Muntiacus muntjac ), sambar deer ( Rusa unicolor ), Malayan sun bear ( Helarctos malayanus ), Malayan gaur ( Bos gaurus ) and Asian elephant ( Elephas maximus ) 1 , 2 , 17 , 18 . In Malaysia, large bodied prey species such as the sambar deer, and smaller prey like the muntjac and wild pig ( Sus scrofa ) have been described as the key ecological determinant of predators such as the Malayan tiger density and their potential habitat 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation